AI in the posthuman art classroom - Pente, Patti; Adams, Cathy (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2023)
This article explores the use of AI-generated art as a way to educate visual art students and teachers about ethical concerns related to artificial intelligence. For example, gender and racial bias in the data sets that artificial intelligence trains on remains a significant concern. Art educators can proactively address these issues by supporting their students in understanding the ethical issues surrounding AI that will continue to arise. We advocate for a posthuman approach to AI, treating it not as a mere tool but as a collaborator in the creative process. Through an examination of AI-artists who critique AI, we show that AI-artmaking has the potential to be a valuable addition to the art classroom, allowing both students and teachers to explore and grapple with the ethical challenges associated with AI.